Improving the safety and efficiency of outpatient lumbar puncture service - Mark Sweeney; Adam Al-Diwani; Robert Hadden (BMJ Open Quality)
AbstractLumbar puncture (LP) is a commonly performed procedure in diagnosis and management of neurological conditions. LP is generally safe, however there are a number of potentially serious complications, including epidural haematoma and cerebral herniation. The risks of these should be considered and minimised prior to undertaking LP.Our regional neuroscience centre provides an outpatient LP service for patients throughout southeast England. Referrals from distant hospitals meant there was frequently no access to important clinical information, including indication for LP, past medical history, or medication history until the day of the procedure, and no access to results of investigations such as coagulation profile, platelet count, or intracranial imaging. Furthermore, there was limited capacity or time available in the day ward to perform these tests prior to LP. As a result, patients were either having LPs cancelled on the day of the procedure, were delayed by several hours on the day of the procedure for investigations, or were subject to the risk of having the LP performed without the knowledge of these key safety indicators.To address this issue we implemented an LP safety checklist to be completed by referring neurologists, providing details of the patient’s medical history and results of investigations performed locally. In doing this, we increased the proportion of patients with an available platelet count prior to LP from 25% to 89%, and available coagulation profile from 18% to 82%. In addition, we saw a qualitative increase in the confidence of junior doctors in the safety of the LP clinic, as measured by a survey taken before and after the implementation of this system.This simple intervention made a rapid and remarkable difference to the safety and efficiency of this outpatient LP clinic. We would encourage other units to adopt this approach to address similar problems in a variety of outpatient settings.